Management accounting practices and organization performance: a case study of craft company / Nor Azlina Ab Rahman - Ab Rahman, Nor Azlina (2019)
Technology advances, competitive rivalry and new innovation have changed the business world. In this context, this research areas of concern additionally have been the causes to adopt management accounting practices (MAPs) in small and medium sized enterprises (SMEs). The purpose of this research is to explore and explain the uptake of a broad range of MAPs in driving the performance of the case study company within Malaysian Craft Industry. Thus, this research also aims to determine the factors that facilitate or impede the MAPs, and its effects on organization performance. Qualitative research approach using a single case study method was adopted for the data collection. The data was collected from multiple sources of evidence which comprised of semi-structured interviews, documentation review, observation and archival records. In-depth interviews were conducted with 16 personnel of the case company. Data were analysed using NVivo 12. The case study results revealed that the craft company has comprehensively utilized of management accounting tools and technique which consist of costing, budgeting and decision support system. Further to that, the study found that three factors; entrepreneurship characteristics, best practices and dynamic capabilities, and business strategy have influenced the adoption of traditional MAPs which in turn improved organization’s performance. This study enriches the existing body of knowledge in the management accounting practices by providing information on the adoption of MAPs within SMEs in the Malaysian Craft industry. The finding from this research will increase the understanding of MAPs from SMEs context; thus, it can assist SME entrepreneurs to adopt MAPs in their daily operations to achieve business success. This research will provide guidance for craft industry entrepreneurs by enabling them to adopt MAP, which will enhance and sustain the organization’s performance for the short and long term. The findings also can be specifically informative for policy makers’ intent on developing MAPs skills among Malaysian SMEs. Furthermore, the valuable insights from this research also can revealed the nature of MAPs in a medium size company within the craft industry in a developing country.